Tiflis armourer Khechatur - Levan B. Dvalishvili (Историческое оружиеведение)
Early examples of Tiflis arms have always attracted attention of researchers and admirers of historical arms with their refinement, beauty and a high level of craftsmanship. Unfortunately, there is little information about craftsmen who produced this kind of arms.